2013
DOI: 10.1371/journal.pone.0066595
|View full text |Cite
|
Sign up to set email alerts
|

Scrub Typhus Meningitis in South India — A Retrospective Study

Abstract: BackgroundScrub typhus is prevalent in India although definite statistics are not available. There has been only one study on scrub typhus meningitis 20 years ago. Most reports of meningitis/meningoencephalitis in scrub typhus are case reportsMethodsA retrospective study done in Pondicherry to extract cases of scrub typhus admitted to hospital between February 2011 and January 2012. Diagnosis was by a combination of any one of the following in a patient with an acute febrile illness- a positive scrub IgM ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 47 publications
12
110
3
Order By: Relevance
“…MODS were reported as high as 50% of patients without meningoencephalitis and 76.5% with meningoencephalitis. 19 In our study MODS was present in 7%, meningoencephalitis in 1% and ARDS in 11% patients though other study reported meningoencephalitis as a more common complication (26%) and ARDS incidence same as present study (11.1%). 20 The case fatality rate was 6% of which the most common cause was MODS, followed by ARDS.…”
Section: Discussionsupporting
confidence: 51%
“…MODS were reported as high as 50% of patients without meningoencephalitis and 76.5% with meningoencephalitis. 19 In our study MODS was present in 7%, meningoencephalitis in 1% and ARDS in 11% patients though other study reported meningoencephalitis as a more common complication (26%) and ARDS incidence same as present study (11.1%). 20 The case fatality rate was 6% of which the most common cause was MODS, followed by ARDS.…”
Section: Discussionsupporting
confidence: 51%
“…4 Medical records of patients were reviewed. The clinical manifestations, investigations and outcomes were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…It is widespread in the so-called 'tsutsugamushi triangle' which extends from Pakistan, India, Nepal in the West, to South Eastern Siberia, Japan, China and Korea in the North, to Indonesia, the Philippines, Northern Australia and the Pacific islands in the South. Taiwan is the centre of the tsutsugamushi triangle, and Korea has the highest reported incidence in the world [2]. About one million new cases are identified annually.…”
Section: Epidemiologymentioning
confidence: 99%
“…The eschar not only has immense diagnostic relevance but is also important prognostically. Absence of an eschar is a risk factor for mortality [2].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation